The Potential Use of Citrus aurantifolia L. Essential Oils for Decay Control, Quality Preservation of Agricultural Products, and Anti-Insect Activity - Lucia Galovičová; Petra Borotová; Nenad L. Vukovic; Milena Vukic; Simona Kunová; Pawel Hanus; Przemysław Łukasz Kowalczewski; Ladislav Bakay; Miroslava Kačániová (Agronomy, 2022)
The primary objective of the study was to evaluate the biological activity of Citrus aurantifolia essential oil (CAEO) with emphasis on antioxidant, antimicrobial, and insecticidal activity, chemical composition, and the antimicrobial effect of its vapor phase in situ on various food models. We determined the main volatile components of CAEO as α-phellandrene (48.5%) and p-cymene (16.5%). The antioxidant activity was high and reached 74.5 ± 0.5%, which corresponds to 442 ± 2.3 TEAC. The antimicrobial activity in the contact phase was most pronounced against Gram-negative bacteria, with inhibition zones of 12.66–15.33 mm and a minimal inhibition concentration of 2.36–8.26 µL/mL. The antimicrobial activity of the CAEO vapor phase was high at the highest concentration tested (500 µL/mL), but the inhibitory effect was seen at all concentrations tested. The effect was observed on all types of microorganisms and all types of model foods. Based on the findings, CAEO could find use in storing and extending the shelf life of agricultural products. Insecticidal activity reached 10–90% depending on the concentration used. The significant insecticidal effect provides the possibility of using CAEO as a natural insecticidal, larvicidal, or repellent preparation.